The Bloomsbury handbook of theory in comparative and international education - Jules, Tavis Deryck 1980-; Thomas, Matthew, A. M. (Bloomsbury Academic, 2021)
"This handbook surveys the central theories in comparative and international education (CIE). Each chapter includes an overview of the theory including its history and development, references to examples where the theory has been applied in CIE research and practice, and suggestions for further reading. Written by leading scholars from the USA, the UK, China, Canada, Germany, Australia, Denmark, The Netherlands, Luxembourg and Sweden this is must-have reference work for those studying CIE. The handbook includes chapters on: Structuralism, Colonialism/Imperialism, Marxism, Modernization/Human Capital Theory, World System Theory, Post-Colonialism, Post-Modernism / Post-Structuralism, Post-Socialism/Post-communism/Post-authoritarianism, Feminism/Gender, Post-Foundationalism, Neo-Colonialism and Southern Turn Theory, Neo-liberalism, Neo-Institutionalism, Neo-Marxism, Neo-Realism, Policy Borrowing and Lending and Educational Transfer, Peace Theories, Human Rights, Critical Pedagogy, Transitologies, Actor Network Theory, Communication Theory, Social Network Theory, Capabilities Theory, Cultural Political Economy and Regime Theory."
Keywords: Kulturvergleich; Ausbildung; Bildungstheorie; Comparative education / Cross-cultural studies; International education / Cross-cultural studies; Philosophy & theory of education; Education / Philosophy & Social Aspects; Education / Comparative; Comparative education; International education; Cross-cultural studies; Aufsatzsammlung